Living architectures : a film series - Bêka, Ila; Lemoine, Louise (Paris : BêkaPartners, 2013)
A complete edition of Ila Bêka & Louise Lemoine's series of films that "seeks to develop a way of looking at architecture which turns away from the current trend of idealizing the representation of our architectural heritage."
Films. [disc] 3. Inside Piano. The little Beaubourg. The submarine. The power of silence. Pomerolm Herzog & De Meuron. Interview with Renzo Piano.
Title from container.
Text in English and French.
PAL, all regions.
Includes interviews.
boek